2003
DOI: 10.1054/ijom.2003.0413
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of third molar impaction in a Singapore Chinese population: a retrospective radiographic survey

Abstract: One thousand orthopantomograms (OPGs) of patients 20-40 years old were examined. Where impacted third molars were present, the angle and depth of impaction were recorded. Results were analysed using the Pearson chi2 test. 68.6% of OPGs showed at least one impacted third molar. The frequency was three-fold higher in the mandible (1024/1079=90%) than in the maxilla (306/1077=28%), with a significantly higher frequency (P<0.05) in females (56%) than males (44%). The mesioangular impaction was the most common, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
125
10
18

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(186 citation statements)
references
References 0 publications
33
125
10
18
Order By: Relevance
“…17 But another study showed that the most common position was B (80%). 18 This study supports a study that stated position B was the most common. 19 In the present study, position A was the most common position (62.2%).…”
Section: Discussionsupporting
confidence: 89%
“…17 But another study showed that the most common position was B (80%). 18 This study supports a study that stated position B was the most common. 19 In the present study, position A was the most common position (62.2%).…”
Section: Discussionsupporting
confidence: 89%
“…A study among the Jordanian population 13 found that vertical type of angulation was the most common (61.4%) and mesioangular type was only 18.1%. However, studies among Chinese (80%) and Korean populations (46.5%) showed that mesioangular type of impaction was the most frequently seen 11 . In this present study too, the mesioangular type was the commonly extracted tooth (43.7%).…”
Section: Discussionmentioning
confidence: 98%
“…The occurrence of Vol. The angulation of the third molar to the long axis of the second molar was measured using the method suggested by Quek et al (2003) 11 . Class III third molar is totally embedded in the bone because of lack of space Inclusion Criteria: All the patients included in this study were 18 years and older, as growth is essentially completed by this age along with complete root formation, either being straight, curved or fused.…”
Section: Introductionmentioning
confidence: 99%
“…Impacted premolars were recorded based on Winter's classification systems. The angulations of impaction were measured using the Quek et al (10) method to classify as mesioangular, vertical, distoangular, horizontal and bucco-lingual ( Figure 1). The percentage and number of impacted premolars according to tooth angulations were determined .…”
Section: Methodsmentioning
confidence: 99%
“…Although they are mostly asymptomatic, they are sometimes discovered when a patient presents with pericoronitis or pathologies such as a cystic lesion in an adjacent tooth. Thus, the discovery of an impaction usually occurs during a routine visit, and this leads to a late diagnosis (8)(9)(10). There are insufficient studies about impacted premolar prevalence in the literature.…”
Section: Introductionmentioning
confidence: 99%